Implementasi UU No 18 Tahun 2008 Tentang Pengelolaan Sampah dalam Mengatasi Konflik Sosial Masyarakat yang Terjadi di Sekitar TPA Kecamatan Sambutan - Selviyani Selviyani; Moh Bahzar; Wingkolatin Wingkolatin; A. Hardoko; Jamil, Jamil; Marwiah Marwiah (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
Waste management is a systematic and sustainable activity that includes reducing and handling waste. Social conflict is a social process in which individuals or groups try to fulfill their goals by opposing opposing parties accompanied by threats or violence. The aim of this research is to describe the social conflict that occurs in the community living around the Sambutan District TPA in the form of a foul smell arising from piles of rubbish as well as acts of thuggery experienced by rubbish truck drivers and to describe the implementation of Law Number 18 of 2008 concerning Waste Management in Overcoming Social Conflict Between Communities Around the Sambutan District TPA. Types of qualitative phenomenological research. The research was conducted at the Sambutan District TPA in March 2024- May 2024. The research subjects were one Head of the Sambutan TPA UPTD, one TPA Supervisor and four communities around the Sambutan TPA using observation, interview and documentation techniques. Data analysis techniques are data collection, data reduction, data presentation and data collection. The results of the research show that the implementation of Law Number 18 of 2008 concerning Waste Management in Overcoming Social Conflict between the communities around the Sambutan District TPA shows that the head of the UPTD and the Sambutan TPA Supervisor have carried out waste management in accordance with Law Number 18 of 2008, such as using waste during 3 days to reduce the stench from piles of rubbish and operate rubbish truck drivers at certain hours to avoid acts of thuggery at night, this is to overcome social conflicts between communities around the TPA in Sambutan sub-district